Kontribusi Likuiditas dan Aktivitas Persediaan dalam mendukung Profitabilitas Perusahaan - Nuryani, Anum; Prasetio, Bagus (Universitas Mitra Indonesia, 2025)
This study aims to determine the Effect of Current Ratio (CR) and Inventory Turn Over (ITO) on Return On Asset (ROA) at PT Siantar Top Tbk for the period 2013 to 2023. The research method used is a quantitative method with data analysis techniques used are descriptive analysis, classical assumption test, normality test, microlinearity test, autocorrelation test, heteroscedasticity test, linear regression test, correlation coefficient test, coefficient of determination test partial test (T test), and simultaneous test (F test). The results of the study indicate that partially the Current Ratio variable does not have a significant effect on Return On Asset with a calculated t value (1.318) t table (2.365) and a significance value of 0.224 0.05. The Inventory Turn Over variable partially has a significant effect on Return On Asset with a comparative value of t count (3.320) t table (2.306) and a significance value of 0.011 0.05 and simultaneously the Current Ratio and Inventory Turn Over have a significant effect with a value of F count 8.788 F table 4.46 with a Sig. F value of 0.010 0.05.Keywords : CR, ROA, ITO